Knowledge regarding tobacco cessation among undergraduate, graduate, and postgraduate/faculty in dental colleges of Ludhiana: A survey - Jasmine Grewal; Damanpreet Kaur Isher; Parminder Pal S. Isher (Wolters Kluwer Medknow Publications, 2019)
Aim: The aim of the study is to assess and compare the knowledge regarding tobacco cessation among various educational groups. Materials and Methods: A questionnaire comprising 15 questions was distributed among three educational groups (graduate, undergraduate, and postgraduate/faculty) in dental colleges of Ludhiana. Statistical Analysis: One-way analysis of variance and Student's t-test were used to compare the knowledge among different groups using education level and gender as the variables, respectively. Results: A total of 300 participants (73.17%) completed the survey of which 71 (23.66%) were undergraduates, 160 (53.33%) were graduates, and 69 (23%) were postgraduates/faculty. Statistically significant difference was detected among the three educational groups and gender. Conclusion: Difference in viewpoint was observed on the basis of educational groups and gender. Participants have insufficient knowledge and training for tobacco cessation. Adoption of new measures to stop tobacco consumption is the need of the hour.